Iodimetry method of endogenous deposits search - V V Diakonov; A E Kotelnikov; V E Markov; E E Kotelnikov; N A Gorg (RUDN Journal of Engineering Research, 2013)
The article deals with the theoretical background for the application of iodometry search of endogenous deposits, particularly the behavior of iodine above the ore bodies. Given example of an integrated research of lithogeochemical secondary halos over the porphyry copper deposits and the possibility of using iodometry for chromite ore search.